Experiment Search for a Charged Higgs Boson Produced in the Vector-Boson Fusion Mode with Decay H ± → W ± Z using p p Collisions at √ s = 8 TeV with the ATLAS Experiment - Aad, G. (2015)
A search for a charged Higgs boson, H±, decaying to a W± boson and a Z boson is presented. The search is based on 20.3  fb−1 of proton-proton collision data at a center-of-mass energy of 8 TeV recorded with the ATLAS detector at the LHC. The H± boson is assumed to be produced via vector-boson fusion and the decays W±→qq′¯ and Z→e+e-/μ+μ- are considered. The search is performed in a range of charged Higgs boson masses from 200 to 1000 GeV. No evidence for the production of an H± boson is observed. Upper limits of 31?1020 fb at 95% C.L. are placed on the cross section for vector-boson fusion production of an H± boson times its branching fraction to W±Z. The limits are compared with predictions from the Georgi-Machacek Higgs triplet model.